Collagen and Elastic Fiber Content Correlation Analysis between Horizontal and Vertical Orientations of Skin Samples of Human Body - Naveen Kumar; Pramod Kumar; Satheesha Nayak Badagabettu; Ranjini Kudva; Sudarshan Surendran; Murali Adiga (Hindawi Limited, 2015)
Background. Unequal distribution of dermal collagen and elastic fibers in different orientations of skin is reported to be one of the multifocal causes of scar related complications. Present study is to understand the correlation pattern between collagen in horizontal (CH) and in vertical (CV) directions as well as that of elastic in horizontal (EH) and vertical (EV) directions. Materials and Method. A total of 320 skin samples were collected in two orientations from suprascapular, anterior chest, lateral chest, anterior abdominal wall, and inguinal regions of 32 human cadavers. Spearman correlation coefficient (r) was calculated between the variables (CH, CV, EH, and EV). Results. Significant positive correlation between CH and CV, and between EH and EV observed in all 5 areas tested. A negative correlation between CV and EV at suprascapular, lateral chest, and inguinal regions and negative correlation between CH and EH at anterior chest and anterior abdominal wall have been identified. Conclusion. Knowledge of asymmetric content of dermal collagen and elastic fibers together with the varied strength and degree of association in the given area provides guidelines to the dermatologists and aesthetic surgeons in placing elective incisions in the direction maximally utilizing the anatomical facts for aesthetically pleasing result.